Study on the Two-Dimensional Density Distribution for Gas Plasmas Driven by Laser Pulse - 焦志宏 王国利 周效信 吴朝辉 左言磊 曾小明 周凯南 粟敬钦 (Plasma science & technology, 2016)
We perform an experimental study of two-dimensional（2D） electron density profiles of the laser-induced plasma plumes in air by ordinarily laboratorial interferometry. The electron density distributions measured show a feature of hollow core. To illustrate the feature, we present a theoretical investigation by using dynamics analysis. In the simulation, the propagation of laser pulse with the evolution of electron density is utilized to evaluate ionization of air target for the plasma-formation stage. In the plasma-expansion stage, a simple adiabatic fluid dynamics is used to calculate the evolution of plasma outward expansion. The simulations show good agreements with experimental results, and demonstrate an effective way of determining 2D density profiles of the laser-induced plasma plume in gas.